A Novel Architecture for Fast RSA Key Generation Based on RNS - Jingwei Hu; Wei Guo; Jizeng Wei; Yisong Chang; Dazhi Sun (2011 Fourth International Symposium on Parallel Architectures, Algorithms and Programming, 2011)
RSA key generation is of great concern for implementation of RSA cryptosystem on embeded system due to its long processing latency. In this paper, a novel architecture is presented to provide high processing speed to RSA key generation for embedded platform with limited processing capacity. In order to exploit more data level parallelism, Residue Number System (RNS) is introduced to accelerate RSA key pair generation, in which these independent elements can be processed simultaneously. A cipher processor based on Transport Triggered Architecture (TTA) is proposed to realized the parallelism at the architecture level.In the meantime,division is avoided in the proposed architecture,which reduces the expense of hardware implementation remarkably. The proposed design is implemented by Verilog HDL and synthesized in a 0.18μm CMOS process. A rate of 3 pairs per second can be achieved for 1024-bit RSA key generation at the frequency of 100 MHz.